Description of two new species closely related to Doryctobracon areolatus (Szépligeti, 1911) (Hymenoptera, Braconidae), based on morphometric and molecular analyses - Marinho, Cláudia F.; Cônsoli, Fernando L.; Penteado-Dias, Angélica Maria; Zucchi, Roberto A. (Zootaxa, 2017)
This study clarifies the identity of two morphs that appear similar but not identical to the braconid wasp Doryctobracon areolatus (Szépligeti), by analyses of fore wing morphometry and the ITS2 and D2 region of 28S ribosomal DNA. Wing measurements of D. areolatus and the two morphs, one with a yellow stigma and one with a brown stigma, from several Brazilian localities, were taken and subjected to geometric morphometry. Evaluation of 20 anatomical points on the fore wing by means of multivariate analysis revealed that these morphs consistently differ from D. areolatus. Intraspecific size variation in both molecular markers (ITS2 and 28S-D2 rDNA) was also detected among populations of D. areolatus from the states of Amapá, São Paulo, Goiás, and Tocantins, but no such difference was observed among samples of the two morphs. However, high sequence variability was observed for both markers among D. areolatus and these morphs. Morphometric analysis yielded similar results and produced dendrogram congruent with those based on the molecular markers, also indicating that D. areolatus corresponds to a complex of cryptic species. Therefore, our morphometric and molecular data, in addition to revealing that D. areolatus includes cryptic species, showed that the unidentified morphs actually represent two distinct, previously undescribed species of Doryctobracon. These new taxa are formally described herein, as D. whartoni sp. nov. and D. adaimei sp. nov.